Ilex rotunda Thunb Protects Against Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice by Restoring the Intestinal Mucosal Barrier and Modulating the Oncostatin M/Oncostatin M Receptor Pathway - Li, Yao; Yang, Xu; Yuan, Jia-ni; Lin, Rui; Tian, Yun-yuan; Li, Yu-xin; Zhang, Yan; Wang, Xu-fang; Xie, Yan-hua; Wang, Si-wang; Zheng, Xiao-hui (Frontiers in Pharmacology, 2022)
Ilex rotunda Thunb (IR) is a traditional Chinese medicine used in the clinical treatment of gastric ulcer and duodenal ulcer. However, the effect of IR on ulcerative colitis (UC) and its underlying mechanism remains unclear. The current study aimed to investigate the therapeutic effect of IR on UC mice induced by dextran sulfate sodium (DSS) and illustrate the potential mechanism of this effect. The main components of IR were analyzed by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometer (UPLC-QTOF-MS). And then we established a model of UC mice by drinking 2.0% DSS for 7 days followed by 2 weeks of tap water for three cycles, and administered with IR. On day 56, the disease activity index (DAI), colon length, pathological changes and inflammatory response of colon tissue of mice were assessed. The oxidative stress and apoptosis of colon tissue were detected, and the integrity of intestinal mucosal barrier was also evaluated to illustrate the effect of IR. Otherwise, the relationship between Oncostatin M (OSM) and its receptor (OSMR) signaling pathway and IR treatment of UC was elucidated through mouse model and Caco2 cell model. The results showed that IR significantly alleviates the symptoms of UC, including rescues shortened colon length, reduces DAI score, MPO and LPS content in serum, pathological damage, the infiltration of inﬂammatory cells and mRNA levels of IL-1β, TNF-αand IL-6 in colon tissue, and alleviated the oxidative stress and apoptosis through reduces Keap-1 protein expression and increasing Nrf2 and HO-1 proteins expression, and promote the regeneration of epithelial cells. IR also promoted the recovery of the intestinal mucosal barrier and modulating OSM/OSMR pathway to alleviate UC. In conclusion, IR exerts a therapeutic effect on UC by restoring intestinal mucosal barrier and regulating OSM/OSMR pathway.